2010
DOI: 10.1002/jsfa.4104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and nitrogen fertilisation on triticale grain yield, chemical composition and nutritive value

Abstract: Reducing tillage intensity improved the CP content and CPD of triticale grain. The application of 50 kg N ha(-1) resulted in good grain quality parameters and grain and protein yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
3
32
0
3
Order By: Relevance
“…Oettler et al (2000), ukazuju da veliki broj genotipova tritikalea pokazuje bolju adaptaciju na kiselost u odnosu na sorte pšenice, a Madić et al (2013) ukazuju da tritikale daje zadovoljavajući prinos na kiselom zemljištu. Povećano đubrenje azotom utiče na povećanje prinosa i procenta proteina kod pšenice (Zecevic et al, 2010) i tritikalea (Lestingi et al, 2010). Pored toga, dosta dobre prinose tritikale daje i na većim nadmorskim visinama (Stošović et al, 2010).…”
Section: Uvodunclassified
“…Oettler et al (2000), ukazuju da veliki broj genotipova tritikalea pokazuje bolju adaptaciju na kiselost u odnosu na sorte pšenice, a Madić et al (2013) ukazuju da tritikale daje zadovoljavajući prinos na kiselom zemljištu. Povećano đubrenje azotom utiče na povećanje prinosa i procenta proteina kod pšenice (Zecevic et al, 2010) i tritikalea (Lestingi et al, 2010). Pored toga, dosta dobre prinose tritikale daje i na većim nadmorskim visinama (Stošović et al, 2010).…”
Section: Uvodunclassified
“…One of the most important crop management techniques for spring triticale production is N fertilization (Gülmezoglu, Kinaci, 2004;Janušauskaitė, 2009;Knapowski et al, 2009;Zečevic et al, 2010). Many authors have reported positive effect of N fertilization on grain yield (Gibson et al, 2007;Lestingi et al, 2010). Grain yield can be analyzed in terms of three primary yield components -number of productive ears per unit of land area, grains ear -1 and thousand grain weight (TGW).…”
Section: Introductionmentioning
confidence: 99%
“…Both N rates and application time are important to the development of yield components (Weber et al, 2008;Pecio, 2010). The optimal timing of N application increased grain yield and protein content (Kara, Uysal, 2009;Lestingi et al, 2010). However, Gibson et al (2007) found that N application at a rate higher than 33 kg ha -1 reduced triticale grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…Para o triticale, entre outros fatores, a disponibilidade de nitrogênio é de suma importância para o crescimento inicial, desenvolvimento e produtividade final, além de estar relacionado com a quantidade de proteína encontrada nos grãos, fator que influencia a qualidade do produto (LESTINGI et al, 2010). Contudo, além do grande impacto ambiental causado pela aplicação de fertilizantes nitrogenados (ZAVATTARO et al, 2012), o nitrogênio é um insumo de alto custo para o produtor de triticale (DARTORA et al, 2013).…”
Section: Introductionunclassified